The role of subchondral circulation in the physiology of load transmission - Beverly, M (2018)
Although the blood supply of bone at rest is well defined, the way in which skeletal activity might affect perfusion under active joints has received little attention. Intraosseous pressure (IOP) has been studied for several decades and was thought to be raised in osteonecrosis, arthritis and bone pain but there has been difficulty in defining IOP and using it for clinical purposes. This work aims to explore subchondral physiology during loading and to seek supporting evidence for a specialised subchondral circulation adapted to load transmission. Originally in 1985 IOP was studied in an animal model. IOP at rest was found to be variable and sensitive to measurement technique. It had underlying cardiac, respiratory and circulation waves. It was correlated with blood pressure and had a proportionate pulse pressure (PP). Subchondral IOP was raised by proximal venous occlusion and loading. Steroid treatment increased IOP, probably by reducing intraosseous fat volume. For this thesis in 2014 an in vitro calf foot model was developed and used to further investigate IOP at rest and with combinations of perfusion. The model was then used to study different patterns of loading. Load was found to be transferred partly by hydraulic forces from subchondral to cortical bone through high pressure tolerant tissues. There appeared to be a one way valve within the bone. Previously undescribed upper tibial vascular marks were found on MRI scans. 60 pairs of scans were scored against osteoarthritis (OA) by Kellgren-Lawrence grade on plain x-rays. Vessels were reduced or lost in early OA. A second study of 200 paired X-ray and MRI scans confirmed the initial results and examined the femoral subchondral vascular marks. Axial subchondral histology in animal and human tissue showed the presence of subchondral vessels. The subchondral vascular network was found to be present in healthy bone but absent in osteoarthritis. A subcortical valve like structure appears to exist that might allow high pressure hydraulic force transmission without vascular damage. Finally, other evidence in support of the thesis is advanced. IOP measurement is only a reflection of perfusion conditions in the blood pool at the needle tip. A new understanding of IOP and its use in exploring bone perfusion by a subtraction technique is offered. Load is transferred partly by hydraulic force from the subchondral bone to the cortical shaft. Histologically there are subchondral vessels with possible valves in the subcortical region. A fine subchondral capillary plexus exists under healthy cartilage. Subchondral tissues support hydraulic pressure transmission during weight bearing. Vessels are lost in early OA. Osteoarthritis may be due to failure of vasculo-mechanical circulation in the subchondral region.